TC-enabled and distributed cloud computing access control model - Halboob, Waleed; Mahmod, Ramlan; Alghathbar, Khaled S.; Mamat, Ali (Asian Network for Scientific Information, 2014)
Controlling access to the cloud computing services involves new scalability and security challenges that cannot be directly addressed by traditional access control solutions. In other words, cloud computing access control requires establishing a trust between users, service provider and provided services in a scalable manner. Moreover, several access control issues have not been considered in cloud computing such as providing users with a temporal and delegable access. This paper proposed the design of a trusted and decentralized cloud computing access control model for better security and scalability. To address the scalability issue, the components of the proposed model are separated in such a way that they can be decentralized and executed in different extensible machines. The proposed model includes a Trusted XML-based Cloud Computing Policy Language (TXCCPL) that specifies access control policies for authenticating and authorizing both the user and his platform based on the Decentralized Trust Management (DTM) and Trusted Computing (TC) concepts. An Identity Based Encryption (IBE) is used for providing users with temporal and delegable access. Our analysis shows that the proposed model is cost-effectively distributed while avoiding the possible bottlenecks and, as a result, effectively scales with increased workloads. Also, using the DTM and TC concepts help on addressing several security challenges found in cloud computing.